WILSON DISEASE IN CHILDREN - DIAGNOSTIC CRITERIA AND SCORES - Alexandra Coroleucă; Daniela Păcurar; Coriolan Emil Ulmeanu (Amaltea Medical Publishing House, 2019)
Wilson's disease is a genetic autosomal recessive transmitted pathology, that causes disorders of copper metabolism, leading to its accumulation in target tissues. It is a multisystemic affection and has a polymorphic clinical picture. Establishing a positive diagnosis can be difficult, with no single test that confirms or definitely excludes the disease. Diagnostic criteria for the Wilson disease in adult patients were established, then reevaluated for the child. Establishing early diagnosis allows early chelation therapy, which provides a better prognosis, delaying the progression of the disease. This is the reason why the importance of family screening must be emphasised.